PERSEPSI WISATAWAN NUSANTARA TERHADAP KINERJA SEKTOR PARIWISATA DI DESA WISATA KABUPATEN SLEMAN - Lucia Nurbani Kartika; Purwani Retno Andalas (Fakultas Bisnis UKDW, 2012)
This study was intended to analyze the attributes of tourism villages in Sleman district that were perceived by domestic tourists, to identify the perceptions of domestic tourists on the importance of various attributes of tourism villages in Sleman Yogyakarta, to identify the perceptions of domestic tourists on the performance of tourism villages viewed from various attributes which were considered important by tourists and to describe whether or not there were differences in perceptions of domestic tourists on the importance and performance of various attributes of economic, social and tourism infrastructure in the Tourism Village of Sleman Regency. Respondents of this study were domestic tourists who were visiting tourism villages in Sleman Regency with a sample of 150 people, who were selected using purposive sampling technique. The data analysis technique used descriptive analysis and Importance-Performance analysis. The results of the analysis showed that the attributes of public facilities, tour guides who master the local culture and have communication skills, security of tourist attractions (tourism villages), comfort of tourism villages (organized, clean, complete facilities), tourism information (directions, posts on tourism village gates), friendliness of the local people, and people's understanding of culture and tourism objects are in the